2021
DOI: 10.3390/ma14092341
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Radiant Exposure and Irradiance for Triggering Adequate Polymerization of a Photo-Polymerized Resin Cement

Abstract: This study aimed to establish the minimum radiant exposure and irradiance to trigger an adequate polymerization of a photo-polymerized resin cement. In total, 220 disc-shaped specimens (diameter of 10 mm and thickness of 0.1 mm) were fabricated using a photo-polymerized resin cement (Variolink N-transparent, Ivoclar Vivadent). To investigate the minimum radiant exposure, the specimens were polymerized with radiant exposures of 1, 2, 3, 4, 5, 6, and 18 J/cm2 (n = 20). During polymerization, the irradiance was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…For this experiment, we designed four light-curing protocols, ranked according to the total energy (total energy = irradiance × exposure time): LCP1 > LCP2 > LCP3 > LCP4. The DC and microhardness of resin cement under these four light-curing protocols also conformed to this law; the curing performance was positively correlated with irradiance and exposure time, which is similar to previous research [24,39]. Although the curing performance generally showed this pattern, in some groups, the comparison between groups showed that the difference was not significant.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For this experiment, we designed four light-curing protocols, ranked according to the total energy (total energy = irradiance × exposure time): LCP1 > LCP2 > LCP3 > LCP4. The DC and microhardness of resin cement under these four light-curing protocols also conformed to this law; the curing performance was positively correlated with irradiance and exposure time, which is similar to previous research [24,39]. Although the curing performance generally showed this pattern, in some groups, the comparison between groups showed that the difference was not significant.…”
Section: Discussionsupporting
confidence: 86%
“…Studies show that the material types, thickness, transparency and shade of the ceramic materials can have an effect on the curing light reaching the resin cement [20][21][22]. Higher light intensities or longer exposure times improve the curing performance of resin cements [23,24]. However, most of these experiments are studies on the degree of polymerization of resin cement on a single factor.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the light-curing unit according to the ISO standards is 300 mW/cm 2 with wavelengths of 400-515 nm [21]. However, researchers have reported that the minimum radiant exposure and irradiance to trigger an adequate polymerization of the light-cured resin cement were 6 J/cm 2 and 100 mW/cm 2 , respectively [22]. The light intensity at 200 mW/cm 2 resulted in adequate curing and degree of conversion of luting cement.…”
Section: Discussionmentioning
confidence: 99%